Evaluation of in-vitro and in-silico antidiabetic potential, glucose metabolism, antioxidant, cytotoxicity and phytochemical content of Ipomoea bolusiana Schinz and Ipomoea crassipes Hook tubers - Garland Kgosi More; Nolitha Nkobole; Charmy Twala; Sechaba Machedi; Tebogo Amos Moswetsa; Ramakwala Christinah Chokwe (Phytomedicine Plus)
Background: Diabetes Mellitus is a chronic metabolic disorder caused by genetic disorders and other factors such as the use of certain medications, pancreatic injury, and autoimmune diseases such as rheumatoid arthritis and high blood pressure. However, several therapeutic agents are currently used to manage blood sugar levels, thus reducing the risk of complications. Despite efforts to treat or manage this disease, current therapeutic agents have detrimental side effects, presenting a considerable need to develop new effective drugs with fewer adverse effects. The aim of the study: This study aimed to evaluate the inhibitory capacity of I. bolusiana and I. crassipe plant extracts on α-amylase enzyme and to assess the antioxidant capacity. Furthermore, the evaluation of the cytotoxicity properties and glucose metabolism of the extracts was carried out in RAW 264.7 macrophages, C3A hepatocytes and L6 myoblast cell lines. Methods: In vitro antidiabetic activity was tested with α-amylase enzyme inhibition method and antioxidant activity was evaluated. Furthermore, their ability to quench free radicals was investigated using the 2,2-diphenyl-1-picryhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) free radical scavenging method and the superoxide dismutase (SOD) enzyme scavenging method was investigated. Cytotoxicity and glucose metabolism were measured in macrophage (RAW 264.7), hepatocytes (C3A) and myoblast (L6) cells using the colorimetric test 3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide (MTT). Furthermore, phytochemical characterization and tentative identification was performed using FTIR, 1HNMR and UHPLCOrbitrap HRMS, FTIR, whilst computational studies were also employed to determine the biochemical interaction, antidiabetic and inhibitory potential of the extracts with the α-amylase enzyme. Results: The extracts of I. bolusiana and I. crassipes exhibited moderate inhibitory activity against α-amylase with an inhibitory percentage range of 10.72 – 30.08 %. The extracts did not show cytotoxic effects in the treated cells. The extracts of I. bolusiana and I. crassipes significantly increased glucose uptake in L6 and C3A cell lines. The extracts reduced the DPPH and ABTS radicals, showing a range of IC50 values of 7.35 ± 0.43 - 12.02 ± 0.21 µg/mL. However, the extracts were less toxic to the cells as they showed IC50 values > 20 µg/mL. The phytochemical evaluation demonstrated the presence of phenolics, chlorogenic acids, coumarin glucosides and flavonoids in the extracts, which were docked with the α-amylase enzyme. 5-caffeoylquinic acid exhibited the highest binding energy of -6.829 kcal/mol. Conclusions: This study presents various important phytoconstituents and broad-spectrum activities, including α-amylase inhibitory activity, reduction of oxidative stress, less toxicity, and increased glucose metabolism of methanol extracts of I. bolusiana and I. crassipes as a promising source for the isolation of molecules responsible for antidiabetes activities. The results documented in this study will be valuable leads in the development of therapeutic candidates for diabetes and oxidative stress.